Association Between Hormone Replacement Therapy and Development of Endometrial Cancer: Results From a Prospective US Cohort Study - Liang, Ying; Jiao, Haoyan; Qu, Lingbo; Liu, Hao (Frontiers in Medicine, 2022)
Although hormone replacement therapy (HRT) is associated with endometrial cancer (EC) risk, little evidence assesses the effects of potential effect-modifiers on HRT-related EC with a long-term follow-up. In this large-scale longitudinal cohort study, we tried to evaluate the association between different HRT types/method use and risk of EC and reveal this risk within different body mass index (BMI) group. In overall cohort, 677 EC cases were identified during mean 11.6 years follow-up. Cox proportional hazards regressions were used to estimate multivariable-adjusted hazards ratios (HRs) and 95% confidence intervals (95% CIs) by HRT status (never, former, current) for risk of EC incidence. Current HRT use was not significantly associated with EC risk (HR for current vs. never HRT use: 1.13; 95% CI: 0.92, 1.38) in whole cohort, but presented a dose-response effect on the increased EC risk (HR for >10-year use vs. never HRT use: 1.73; 95% CI: 1.35, 2.21). Moreover, EC risk differed in distinct regimens or subsets (all Pinteraction <0.05). Estrogen-only use was associated with the elevated EC risk (HR for current vs. never HRT use: 1.51; 95% CI: 1.12, 2.04), but women with high BMI (>30 kg/m2) who currently used estrogen-only harbored the decreased EC risk (HR: 0.56; 95% CI: 0.38, 0.82) compared to counterparts without HRT use. Estrogen-only use is associated with increased risk EC risk, and precise monitoring of the EC development for postmenopausal women with long-term HRT use are urgently needed. BMI serves as an important surrogate to assess this risk.